Long‐Term Outcome After Heart Transplantation Predicted by Quantitative Myocardial Blush Grade in Coronary Angiography. Issue 6 (25th April 2013) - Hofmann, N. P.; Voss, A.; Dickhaus, H.; Erbacher, M.; Doesch, A.; Ehlermann, P.; Gitsioudis, G.; Buss, S. J.; Giannitsis, E.; Katus, H. A.; Korosoglou, G.
Abstract The purpose of our study was to investigate whether the quantification of myocardial blush grade (MBG) during surveillance coronary angiography can predict long‐term outcome after heart transplantation (HT). In 105 HT recipients who underwent cardiac catheterization, cardiac allograft vasculopathy (CAV) was assessed visually using the ISHLT grading scale (prospective cohort study). MBG was quantified by dividing the plateau of contrast agent gray‐level intensity (Gmax) by the time‐to‐peak intensity (Tmax). In a subgroup (n = 72), myocardial perfusion index by cardiac magnetic resonance imaging (CMR) was assessed. During a mean follow‐up duration of 2.7 (standard deviation [SD] 1.0) years, 26 patients experienced cardiac events, including 7 with cardiac death and 19 who underwent coronary revascularization. Gmax/Tmax was related to CAV by ISHLT criteria and to subsequent cardiac events. By univariate analysis, patient age, organ age, CAV, MBG and myocardial perfusion index by CMR were all predictive for cardiac events. Multivariable analysis demonstrated that Gmax/Tmax provided the most robust prediction of cardiac death (hazard ratio [HR] = 0.2, 95% confidence interval [CI] = 0.06–0.64, p < 0.01) and cardiac events (HR = 0.52, 95% CI = 0.32–0.84, p < 0.01), beyond clinical parameters and the presence of CAV. Gmax/Tmax is a valuable surrogate parameter of microvascular integrity, which is associated with cardiac death and revascularization procedures after HT.